Formation of Bis Oxadiazole- Azo Ligands and Studying of (Spectral Analysis, Thermal Behavior, Bacterial Behavior, Chemical Properties) - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
Bis oxadiazole – azo   ligands  were synthesized   via  many  chemical  reactions  and   steps  represented  by  reaction  between  diamine  aromatic  compound  with concentration  hydrochloric acid  and sodium nitrite   in azotation  reaction as  a first  step , then  the  second  step  involved  coupling   step  to  yield  mainly  compound  containing  di active  groups , which  will  react  with  semicarbazide  in  cyclization  step  to  formation  first  ligand , after  that  preparation  other  ligands    through  various  reaction  like  insertion  reaction  to  yield  second  ligand , azotation  reaction  to  yield  third  ligand  and  substitution  reaction  like  fourth  and  fifth  ligands.  The  prepared   ligands  have  been   identified   by  spectral  techniques  like (1H NMR , FT.IR  and  UV-Visible  spectra)  with  chemical  studies   like  thermal  behavior , physical properties , TLC – Paper , and  biological  studying  like   microbial  assay. Keywords: Oxadiazole, Semicarbazide, amide, Cyclization , Azo, Insertion , Thiazane.